Constraints to Economic Development and Growth in the Middle East and North Africa - Juliane Brach (German Institute of Global and Area Studies (GIGA), 2008)
When comparing the speed and extent of economic development in different geographic regions of the world over the past 20 years, the under-average performance of Arab countries in general and Arab Mediterranean countries in particular is striking. This is despite an overall favorable geo-strategic situation at the crossroads of three continents, with excellent connections to sea and waterways and in direct proximity to the European Union, one of the world's economic hubs. It is also despite the minor importance of negative factors such as a high-burden diseases or high levels of ethnic fractionalization. In this paper, I focus on identifying the most important constraints on Arab Mediterranean economic development. I use state-of-the-art econometric tools to quantify constraints that have been identified through economic theory and studies of the political economy characteristics of the region. The empirical results offer support for the central hypothesis that limited technological capacities and political economy structures are the primary constraints on economic development. With a view to international structural adjustment efforts, my findings imply that the limited success of the Euro-Mediterranean policy to stimulate the economic development of the Arab Mediterranean countries might be because structural adjustment efforts do not tackle - or at least do not sufficiently tackle - these constraints. – – Vergleicht man Geschwindigkeit und Umfang der wirtschaftlichen Entwicklung der verschiedenen Weltregionen in den vergangenen zwanzig Jahren, so fällt insbesondere das unterdurchschnittliche Abschneiden der arabischen Länder im Allgemeinen und der arabischen Mittlemeerländer im Besonderen ins Auge, und dies trotz einer insgesamt vorteilhaften geographischen Lage im Schnittpunkt dreier Kontinente mit exzellenten Anschlussmöglichkeiten an See- und Wasserwege, trotz der direkten Nachbarschaft zum Weltwirtschaftsdrehkreuz Europäische Union und trotz der relativ geringen Bedeutung wichtiger entwicklungshemmender Faktoren, beispielsweise ethnische Zersplitterung oder massive Ausbreitung von Krankheiten wie AIDS oder Malaria. In diesem Aufsatz wird versucht, von den unterschiedlichen Hemmfaktoren wirtschaftlicher Entwicklung, die in der wirtschaftstheoretischen Literatur und/oder in MENA-Regionalstudien diskutiert werden, diejenigen herauszuarbeiten, die wirtschaftliche Entwicklung am stärksten behindern oder möglicherweise stärker als andere. Dabei benutze ich modernste ökonometrische Verfahren, um den Einfluss der verschiedenen erklärenden Variablen zu quantifizieren. Die Ergebnisse stützen die Eingangshypothese, dass insbesondere mangelnde technologische Kapazitäten und Fähigkeiten sowie regionalspezifische politökonomische Strukturen die wirtschaftliche Entwicklung in den arabischen Mittelmeerländern behindern.
Keywords: F50; O10; O53; C30; 330; economic development; quantitative analysis; political economy; Arab countries